Joys of achievement - "Lala, R.M" (New Delhi, 1997)
An entertaining, intimate and deeply moving portrait of the legendary industrialist. For six decades J.R.D. Tata headed India's largest industrial conglomerate with uncommon success. This was only one aspect of his life.
Keywords: Biography- J R D Tata